Scientific masculinities (Chicago, Illinois)
iv, 302 s.
Keywords: "This volume of Osiris integrates gender analysis with the global history of science and medicine from the late Middle Ages to the present by focusing on masculinity. The premise is that social constructions of masculinity function simultaneously as foils for femininity and as methods of differentiating between “kinds” of men. In exploring scientific masculinities, the book asks: how has masculinity been defined, and what are the mechanisms by which it operates in science? The essays are divided into sections that emphasize the importance of gender to the practices of professionalization, the spaces in which scientific, technological, and medical labor is performed, and the ways that sex, gender, and sexual orientation are measured and serve as metaphors in society and culture." --